Pharmacokinetics and Pharmacodynamics of Anidulafungin for Experimental Candida Endophthalmitis: Insights into the Utility of Echinocandins for Treatment of a Potentially Sight-Threatening Infection - Livermore, J. L. (American Society for Microbiology, 2013)
Candida chorioretinitis and endophthalmitis are relatively common manifestations of disseminated candidiasis. Anidulafungin is increasingly used for the treatment of disseminated candidiasis, but its efficacy for Candida endophthalmitis is not known. A nonneutropenic model of hematogenous Candida endophthalmitis was used. Anidulafungin at 5, 10, and 20 mg/kg was initiated at 48 h postinoculation. The fungal densities in the kidney and vitreous humor were determined. Anidulafungin concentrations in the plasma and vitreous humor were measured using high-performance liquid chromatography (HPLC). A pharmacokinetic-pharmacodynamic model was used to link anidulafungin concentrations with the observed antifungal effect. The area under the concentration-time curve (AUC) associated with stasis was determined in the both the kidney and the vitreous humor. The results were bridged to humans to identify likely dosages that are associated with significant antifungal activity within the eye. Inoculation of Candida albicans resulted in logarithmic growth in both the vitreous humor and the kidney. The pharmacokinetics of anidulafungin were linear. There was dose-dependent penetration of the anidulafungin into the vitreous humor. The exposure-response relationships in the kidney and vitreous were completely discordant. AUCs of 270 and 100 were required for stasis in the eye and kidney, respectively. The currently licensed regimen results in an AUC for an average patient that is associated with stasis in the kidney but minimal antifungal activity in the eye. We conclude that anidulafungin penetrates the eye in a dose-dependent manner and that dosages higher than those currently licensed are required to achieve significant antifungal activity in the eye.